A Study of the Fruit Bat (Rousettus sp) Brain Anatomy as Natural Reservoir Wild Animal for the Rabies Virus - Karina Mayang Sari; Siti Khomariyah; Nur Arofah; Sabrina Wahyu Wardhani; Tri Wahyu Pangestiningsih (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2014)
Rousettus sp. (Fruit bat) is one type of fruit bats in Indonesia and act as a natural reservoir of rabies. Rabies is caused by a virus from genus Lyssavirus, family Rhabdoviridae, which attack central nervous system (CNS).The brain is an organ that is sensitive to rabies infection. The purpose of this study was to determine the anatomical structure of the fruit bat brain macroscopically. Five fruit bat were used in this study, they were anaesthetized using ketamine and xylazin. Animals were perfused using physiological saline and 10% buffered formalin. Brains were taken using tweezers after all the bones of the skull were separated. Analysis of macroscopic brain was done descriptively. The results showed that the fruit bat brain were generally divided into cerebrum, cerebellum and brain stem. Gyrus, sulcus and the paraflokulus lobes of the fruit bat brain were less developed than that of the dogs brain.